How Important is Commercial Record Centre to the Information Industry in Malaysia? - Farah Azizzat Wan Nasrudin, Wan; Farik Mat Yatin, Saiful; Shafarin Shaari, Mohd; Nuruain Abu, Siti; Nurhidayah Wan Mohd Hatta, Wan; Hussin, Nurussobah; Zairul Masron, Mohd (International Journal of Engineering and Technology, 2018)
Commercial Records Centers (CRC), a potential business in records management services offer lot of opportunities for those who aware of the advantages. This is a good opportunity arise at the center of entrepreneur aspirations with economic and social conditions to create a new service, either in an existing market or a new one. Efficient administration of an organization and a good business are amongst the reflects of a great records management. Records management are one of the essentials instrument to smoothen administration process, providing data to plan and making decision, also a proof of transaction and existence.Â Being an expert in business for any period of time, one will know that the archiving of business recordsâ€™ is the most important thing. This article will discuss the potential of CRC, clarifying the strategy of marketing and the challenges face by this information industry in MalaysiaÂ Â